Canadianisms and their treatment in dictionaries. - Hamilton, Sandra A. M. (University of Ottawa (Canada), 1997)
Although Canada is a bilingual country, with both French and English as its official languages, Canadians do not have at their disposal, many Canadian-produced general English or French dictionaries. Moreover, they do not have a single general bilingual English-French, French-English dictionary of Canadian origin.$\sp1$ This means that Canadians often use European-produced dictionaries, such as the Nouveau Petit Robert, the Random House Webster, the Robert Collins Super Senior and the Oxford Hachette. Since these dictionaries are not produced for the Canadian market, there are many elements of English and French as used in Canada (i.e. Canadianisms) that are not contained in them. In addition, for the limited number of Canadianisms that are covered, the coverage given by these dictionaries is often unsatisfactory. This thesis studies Canadian English and French to obtain a clearer picture of their nature, and more specifically, of Canadianisms. It then examines current unilingual and bilingual dictionaries produced both in Canada and in Europe, with the objective of determining their coverage and treatment of Canadianisms. From this examination springs a discussion of the problems identified, along with proposed solutions. Finally, the methodology of the Bilingual Canadian Dictionary Project is analyzed in order to see how it deals with Canadianisms, and an actual entry is produced following its methodology to see if this Canadian lexicographic project is meeting its objective of presenting a true account of English and French as they are used in Canada. ftn$\sp1$The only Canadian bilingual dictionary ever produced was Vinay et al.'s Canadian Dictionary published in 1962. This dictionary, however, was only an abridged edition and has long been out of print.
Keywords: Language, Linguistics.